2019
DOI: 10.1186/s13020-019-0233-1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the functions and biomarkers of Codonopsis pilosula and Astragalus membranaceus aqueous extracts in hepatic cells

Abstract: BackgroundHomeostasis is a crucial concept used to describe the condition of patients and the roles of herbs in traditional Chinese medicine. Qi-deficiency pattern is one of the conditions when loss of homeostasis and is usually characterized by symptoms including lassitude, spontaneous sweating, and a weak pulse, which are not easy to quantitate. Codonopsis pilosula and Astragalus membranaceus were usually prescribed for carriers with hepatitis and patients with metastatic colon cancer, because these patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…10 It was proposed that C pilosula restrained hepatocellular carcinoma via GDF15 and HMOX1. 11 Lobetyolin also presented cytotoxic activity against lung cancer. 12 Although there was limited literature focused on the pharmacological effect of Lobetyolin on colon cancer, we assumed that Lobetyolin might function as a therapeutic candidate for colorectal tumour.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…10 It was proposed that C pilosula restrained hepatocellular carcinoma via GDF15 and HMOX1. 11 Lobetyolin also presented cytotoxic activity against lung cancer. 12 Although there was limited literature focused on the pharmacological effect of Lobetyolin on colon cancer, we assumed that Lobetyolin might function as a therapeutic candidate for colorectal tumour.…”
Section: Discussionmentioning
confidence: 98%
“…Codonopsis pilosula component inhibited the cancer cell proliferation and migration . It was proposed that C pilosula restrained hepatocellular carcinoma via GDF15 and HMOX1 . Lobetyolin also presented cytotoxic activity against lung cancer .…”
Section: Discussionmentioning
confidence: 99%
“…A membranaceus has been commonly used as a hepatoprotective drug. [11,12] In a study of 86 patients with CKD, A membranaceus treatment for 3 months was observed to significantly decrease serum creatinine levels in patients, [13] indicating improved kidney function. A review of studies on the effects of A membranaceus on kidney function had reported that it had significantly reduced the serum creatinine especially in patients with baseline serum creatinine level at >133 μmol/L, [14] or 1.52 mg/dL.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…C. pilosula major components are Sterol, triterpenes, glycosides, alkaloids, polysaccharides (14). A couple of hundred years ago, the effectiveness and safety of C. pilosula for the therapy of chronic obstructive lung disease have been successively evaluated (15), and these have led to its utilization for treating patients having that disease (16). Occasionally, its roots can be used as a replacement for ginseng therapy (2).…”
Section: Importance Of Codonopsis As a Medicinal Plantmentioning
confidence: 99%